High-density Seismic Network for Monitoring Alentejo Region (Portugal) and Mitidja Basin Region (Algeria) - Manso, M. (2022)
The seismic sensor network Alentejo (SSN-Alentejo) developed by the Earth Sciences Institute (Instituto de Ciências da Terra, University of Évora) brings the largest high-density seismic sensor network ever deployed in Portugal. This novel network aims to improve the characterization of seismic activity in the region, through a high-resolution mapping of seismic clusters and known faults. Over the next two years, SSN-Alentejo will deploy a monitoring network of 300 sensors, combining high-sensitive sensors with low-cost sensors. SSN-Alentejo augments existing sensing and monitoring capabilities, enabling the opportunity to observe, for the first time in Portuguese territory, live seismic activity in high resolution. Moreover, seismogenic zones such as the Mitidja or Chleff basins in Algeria will also benefit from having a high-density network.